Call for a Spatial Classification of Banking Systems through the Lens of SME Finance - Decentralized versus Centralized Banking in Germany as an Example - Stefan Gärtner; Franz Flögel (Institut Arbeit und Technik (IAT), 2014)
We are calling for comparisons of banking and banking systems from a spatial perspective. Therefore, this paper develops a classification identifying decentralized and centralized banking according to two characteristics: geographical market orientation (regional vs. supraregional) – to determine whether banks facilitate regional savings-investment cycles – and place of decision-making (proximity vs. distance) – to identify whether the flow of soft information is supported in SME lending. The degree of banks' centralization is also approximated by the spatial concentration of bank employees and shows remarkable explanatory power in Germany, as de-centralized banks increase lending at the expense of centralized banks.
Keywords: G21; P51; R51; O16; 330; comparing banking systems; SME finance in Germany; savings and cooperative banks; decentralized vs. centralized banking